Classroom as Community - Ode Yahyu Herliany Yusuf; Wa Ode Rahmadani; Fellyn Elfani; Meutia Septiani; Wa Neti (CV. Rayyan Dwi Bharata, 2023)
The class is a room that is included in the school building, which functions as a place for face-to-face activities in the process of teaching and learning activities. In a class there are students who differ in terms of knowledge, learning speed, and learning styles. They differ in ethnicity, culture, social class and gender. These differences can have important implications for school teaching, curriculum, policies and practices. This is what makes the teacher able to accept, accommodate, and appreciate the diversity of students in a community in the classroom to achieve the same goal. An educator must create a positive classroom environment where all students feel welcome and are involved in classroom learning. Community is one important aspect that must exist in every class. Community can be interpreted as a group consisting of teachers and students in the classroom and interact in teaching and learning activities. An effective teacher will strive so that in the learning he carries out an effective community is formed as well. The community that exists in a class in a learning activity will greatly influence student involvement in the learning process, and ultimately the achievement of learning objectives. The concept of this community is a learning result obtained from sharing between students and teachers, students and students about a material.